2002
DOI: 10.1165/ajrcmb.26.4.4749
|View full text |Cite
|
Sign up to set email alerts
|

Lung Macrophage–Epithelial Cell Interactions Amplify Particle-Mediated Cytokine Release

Abstract: Interactions between alveolar macrophages (AMs) and epithelial cells may promote inflammatory responses to air pollution particles. Normal rat AMs, the alveolar type II epithelial cell line RLE-6TN (RLE), or cocultures of both cell types were incubated with various particles (0-50 microg/ml) for 24 h, followed by assay of released TNF-alpha and MIP-2. The particles used included titanium dioxide (TiO2), alpha-quartz (SiO2), residual oil fly ash (ROFA), or urban air particles (UAP). For all particles, a dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 32 publications
8
73
1
Order By: Relevance
“…There are, of course, other cells present in intact lungs that may independently provide an additional response or alter the response seen by alveolar macrophages. It is known, for example, that macrophage-epithelium interactions enhance the innate immune cytokine response to hyperoxia, particulants, and other toxins (8,16,17,25,28). We deliberately limited our studies to the interaction of spores with macrophages and diminished possible effects of germinated bacteria by using gentamicin in the medium.…”
mentioning
confidence: 99%
“…There are, of course, other cells present in intact lungs that may independently provide an additional response or alter the response seen by alveolar macrophages. It is known, for example, that macrophage-epithelium interactions enhance the innate immune cytokine response to hyperoxia, particulants, and other toxins (8,16,17,25,28). We deliberately limited our studies to the interaction of spores with macrophages and diminished possible effects of germinated bacteria by using gentamicin in the medium.…”
mentioning
confidence: 99%
“…IP-10 was found in both epithelial cells and macrophages, suggesting that both types of cell participate and cooperate in the innate immune response that is responsible for the influx of inflammatory cells seen in Ad7 infection, and both cell types produce IP-10 in other systems (Pechkovsky et al, 2005;Tibbles et al, 2002;Zaiss et al, 2009). It has been shown that interactions between macrophages and epithelial cells promote inflammatory responses to hyperoxia, particulates and other toxins (Drumm et al, 2000;Hjort et al, 2003;Lee & Rannels, 1996;Sharma et al, 2004;Tao & Kobzik, 2002). Elegant work by D'Angio and co-workers demonstrated that cell-cell contact of THP-1 monocyte/macrophages and A549 epithelial cells is important for extracellular and intracellular IL-8 induction by hyperoxia in co-cultured THP-1 cells (Hjort et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar epithelial cells and alveolar macrophages in cocultures released inflammatory cytokines at lower concentrations of TiO 2 NPs than did the respective monocultures. 127 At the expense of greater complexity, these systems could increase the sensitivity of immunotoxicity in vitro screening and enable exposurespecific testing. However, until a correlation of these findings in these systems to data obtained in humans has been shown, their value remains elusive.…”
Section: Guidelines For Sample Preparation and Exposurementioning
confidence: 99%